2015
DOI: 10.1016/j.canlet.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous suppression of the MAP kinase and NF-κB pathways provides a robust therapeutic potential for thyroid cancer

Abstract: The MAP kinase and NF-κB signaling pathways play an important role in thyroid cancer tumorigenesis. We aimed to examine the therapeutic potential of dually targeting the two pathways using AZD6244 and Bortezomib in combination. We evaluated their effects on cell proliferation, cell-cycle progression, apoptosis, cell migration assay, and the activation of the MAPK pathway in vitro and the in vivo using tumor size and immunohistochemical changes of Ki67 and ppRB. We found inhibition of cell growth rate by 10%, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
(52 reference statements)
1
19
0
1
Order By: Relevance
“…Bortezomib, currently approved for the treatment of advanced multiple myeloma, is a proteasome inhibitor and can effectively control canonical and non-canonical NF-κB signaling (Garrean et al 2007, Hideshima et al 2007. Although Bortezomib alone has a modest effect on advanced TC (Bailey et al 2001, Cooper et al 2006, Putzer et al 2013, Tsumagari et al 2015, a synergetic effect was suggested in combination with other chemotherapeutic agents, portending a promising role for Bortezomib in combination therapy regimens (Smith et al 2001, Cooper et al 2006, Mitsiades et al 2006, Tsumagari et al 2015. These observations demonstrate the potential for targeting NF-κB for treatment in resistant and aggressive TC.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bortezomib, currently approved for the treatment of advanced multiple myeloma, is a proteasome inhibitor and can effectively control canonical and non-canonical NF-κB signaling (Garrean et al 2007, Hideshima et al 2007. Although Bortezomib alone has a modest effect on advanced TC (Bailey et al 2001, Cooper et al 2006, Putzer et al 2013, Tsumagari et al 2015, a synergetic effect was suggested in combination with other chemotherapeutic agents, portending a promising role for Bortezomib in combination therapy regimens (Smith et al 2001, Cooper et al 2006, Mitsiades et al 2006, Tsumagari et al 2015. These observations demonstrate the potential for targeting NF-κB for treatment in resistant and aggressive TC.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, new alternative therapies are needed for aggressive TCs. NF-κB has been shown to play a key role in TC by controlling the proliferative and anti-apoptotic signaling pathways of TC cells, including ATCs (Cooper et al 2006, Hsu et al 2014, Tsumagari et al 2015. Paclitaxel induces cell survival through NF-κB activation in ATCs, and the combination of paclitaxel and the NF-κB inhibitor dehydroxymethylepoxyquinomicin has been suggested to compensate for paclitaxel resistance in ATCs (Durante et al 2006, Polona et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…S1A) that we and others have shown to be important for Ret signaling (4,(10)(11)(12). Also included in the panel were inhibitors targeting the proteasome, histone deacetylases, Hsp90, whose effects are more systemic and have shown promise as therapies in different cancer paradigms, including thyroid cancer (13)(14)(15). A couple of these broad-acting inhibitors are clinically approved: bortezomib (multiple myeloma) and vorinostat (T-cell lymphoma).…”
Section: Sorafenib Altered Cellular Network In a Drosophila Ret 2b Mmentioning
confidence: 99%
“…Although EGFR family comprises four members4, deregulation of growth-factor signaling due to hyper-activation of EGFR and HER-2 has been primarily seen in several cancer types5678. However, EGFR inhibitors face three predicaments: 1) Even EGFR is inhibited, the overexpress of HER-2 can still open the downstream pathway9; 2) Point mutation of EGFR exons 19 and 20 may cause reduced sensitivity to drugs10; 3) A tremendous downstream pathway may cause toxicity111213. Thus, unique HER-2 inhibitors with high selectivity and low toxicity, instead of pan blockers14, become critically significant151617.…”
mentioning
confidence: 99%